Optimasi Arus Dan Tegangan Pada Alat Anodizing Portable - Purwanto, Sugeng (SUTET, 2019)
Anodizing process is a process that aims to strengthen the natural protective layer of metals so that the metal becomes a material that is resistant to rust and scratch by using electrolyte solutions and strong DC currents that help the occurrence of chemical reactions. The anodizing process is strongly influenced by current and voltage, the greater the current and voltage, the thicker the oxide layer that occurs on the aluminum surface and the hardness (hardness) will also increase so that the material becomes rust resistant, scratch resistant and if given an organic coating easy to fade or peel off. Optimization of current and voltage on portable anodizing devices will add value to the quality (quality value) of these materials.